Fuzzy Techniques For Contrast Enhancement Of Mammograms - Oo, Chin Hong (Universiti Sains Malaysia, 2011)
Breast cancer is the number one disease among women in the world. Primary prevention seems impossible since the causes of breast cancer still remains unknown. However, early detection is the best defensive against breast cancer and it becomes the key to reduce the mortality rate of breast cancer. Today, X-ray mammography becomes the most common method of detecting breast cancer. However, mammography images are still notoriously difficult to interpret due to the fuzzy nature of the mammograms and the low contrast between the breast cancer and its surroundings. Hence, mammogram contrast enhancement is critical and essential in the tasks of mammography images interpretation. In this study, an approach to mammogram contrast enhancement based on fuzzy techniques is build by using C++ Builder. The application is an integration of conventional and fuzzy enhancement techniques. The conventional techniques that are used are linear contrast, power-law transformation, contrast stretching and unsharp mask while the fuzzy enhancement techniques used are FHH, INT FIT and PD. The project implementation consists of three steps; there are image pre-processing by using conventional enhancement techniques, fuzzy enhancement and the last is performance analysis that uses qualitative and quantitative analysis to evaluate the enhanced mammograms. Overall, all fuzzy enhancement techniques are able to enhance the contrast of the mammograms. However, both FHH and INT techniques are better than FIT and PD since FHH and INT can preserve the information contained in mammograms well compared to FIT and PD.